Enhancing Students Cognitive Abilities in Integrated Islamic High Schools: A Need-Based Analysis for Developing Chemistry Modules Infused with Islamic Values - Ninik Andriyani; Muhamad Subhi Apriantoro (Ethica: International Journal of Humanities and Social Science Studies, 2023)
From an Islamic perspective, motivation to learn and achievement goes hand in hand with faith and piety. Integrated chemistry learning with Islamic values at the Integrated Islamic School is a learning innovation to improve students' cognitive abilities. This research aimed to analyze the needs of students in the integrated chemistry module of Islamic values to upgrade students' cognitive abilities. This study used the descriptive qualitative method. Data was taken from 112 students of class X Integrated Islamic High School in Surakarta. Data were collected using observation, interviews, questionnaire sheets, and analysis of teaching materials. The results of student and teacher interviews show that integrating Islamic values in each subject will increase student interest and motivation in learning. This is in line with the Integrated Islamic school's vision and mission and is supported by more dominant Islamic activities. Structured learning models integrated with Islamic values are believed to be learning innovations that can improve learners' cognitive abilities, skills, and attitudes as a whole. However, the analysis of teaching materials used in the Integrated Islamic School has not supported achieving the above objectives. As a result, it is necessary to develop a chemistry module with a constructivist approach integrated with Islamic values.